Soil spreading of liquid olive mill processing wastes impacts leaching of adsorbed terbuthylazine. (August 2016) - Aharonov-Nadborny, R.; Raviv, M.; Graber, E.R.
Abstract: Olive mill waste water (OMWW) is a major byproduct of the three phase olive oil production process. OMWW has high acidity (pH ∼ 4–5), high salt content (EC ∼ 5–10 mS cm −1 ), extremely high biological and chemical oxygen demand (BOD and COD up to 100, 000 and 220, 000 mg L −1, respectively), and also high concentrations of organic compounds such as phenols and polyphenols. As a result, OMWW cannot be freely discharged into domestic wastewater treatment plants, but on-site treatment is very expensive and not sufficiently effective. Uses for OMWW such as agricultural recycling and co-composting were found to be impractical or expensive. Thus, OMWW is frequently spread on agricultural land for disposal. However, excessive or uncontrolled spreading of such organic-rich and saline wastewater could have many deleterious effects on soil quality, including salinization, phytotoxicity, or contaminant movement. The impact of OMWW on the leaching of adsorbed terbuthylazine, a soil-applied herbicide, was tested in four soils of varying physical and chemical properties. Although terbuthylazine solubility in OMWW is significantly higher than in water, leaching of adsorbed terbuthylazine from OMWW-treated soils was less than from control treatments. Low soil organic carbon and clay contents were major factors that contributed to reduced terbuthylazine leaching after soil treatment with OMWW. Highlights: OMWW is frequently spread on agricultural land for disposal. OMWW effect on leaching of adsorbed terbuthylazine was tested in four soils. Terbuthylazine solubility in OMWW is significantly higher than in water. Terbuthylazine leaching from OMWW-treated soils is lower than control treatment. Low soil organic carbon and clay contribute to reduced terbuthylazine leaching.